ANALISIS FAKTOR INTERNAL DAN EKSTERNAL YANG MEMPENGARUHI TOTAL DANA PIHAK KETIGA (DPK) BANK UMUM SYARIAH DI INDONESIA (Studi pada Bank Umum Syariah Periode 2011-2013) - Septi Wulandari; Siti Aisjah (Jurnal Ilmiah Mahasiswa FEB, 2013)
The purposes of this research are to examine the influence  of  profit  sharing  rate, number of Islamic bank’s branch offices, Gross Domestic Product and inflation  on  third party fund of Islamic banking in Indonesia.  The population in this study is the Islamic banks. This research used secondary data by quarterly financial reports that Islamic bank’s in the Indonesia bank's website. Samples of this  research consist of 3 Islamic  banking that listed in Islamic  banking  statistic in the Indonesia Bank’s website during  the period of  first quarter 2011  to  second quarter 2013.3 Islamic banking is Bank Syariah Mandiri (BSM), Bank Muamalat Indonesia (BMI), and Bank Syariah Mega Indonesia (BSMI). This research is used multiple regression as analysis model.  The results of research using the F test, indicate that the profit sharing rate, number of Islamic bank’s branch offices, Gross domestic product and inflation, simultaneously have significant effect on the total third party funds sharia banks in Indonesia. Research using the t test,  that the profit sharing rate, partially have effect on the total  third party  funds Islamic banks in Indonesia, while a variable number of Islamic bank’s branch offices, gross domestic product and inflation have no effect on the total deposits sharia banks in Indonesia. Variable profit sharing rate has a dominant influence on the total third party funds. Variation in total deposits  that can be explained by a variable  profit sharing rate, number of  Islamic bank’s branch offices, Gross domestic product and inflation in the regression  equation by 32.8%, while the remaining 67,2% is explained by other variables outside the model equations. Key words:  profit  sharing  rate, number of  Islamic bank’s branch offices, gross domestic product, inflation, Third  Party Fund, Islamic bank in Indonesia, multiple regression.